Mayer-Rokitansky-Kuster-Hauser Syndrome (MRKH Syndrome)- An unusual case of primary amenorrhoea (Indian Journal of Case Reports, 2022)
The onset of mestruation is a significant milestone of sexual maturation in a girl child.Although there are numerous causes of primary amenorrhoea, Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, also known as Müllerian aplasia is one the extremely rare cause of primary amenorrhoea which is usually picked up by suitable imaging technique like Magnetic Resonance Imaging (MRI). MRKH is a rare congenital disorder that is characterised by aplasia of the uterus and upper part of the vagina with normal secondary sexual characters and a normal female karyotype (46,XX). The diagnosis is often made during adolescence following investigations for primary amenorrhea and has an estimated prevalence of 1 in 4500 live female births. MRKH syndrome is classified as type I (isolated utero-vaginal aplasia) or type II (associated with extra-genital manifestations also called Müllerian Renal Cervico-thoracic Somite (MURCS) association). No specific treatment is known for this entity except for vaginoplasty for sexual gratification. A case of MRKH Syndrome is reported here where a 16 year old female child presented with primary amenorrhoea.The diagnosis was made initially on clinical suspicion by normal growth with normal secondary sexual characters with failure to achieve menstruation at the age of 16 years, which was confirmed later by MRI Pelvis showing absence of uterus and normal ovaries and blind vaginal canal was visualised and no other renal or spinal anomalies noted. Karyotyping done revealed normal karyotype, 46 XX.